THE ROLE OF INTRINSIC MOTIVATION AS A MEDIATOR BETWEEN RESPONSIBLE LEADERSHIP, WORKLOAD, AND ORGANIZATIONAL CULTURE ON SUSTAINABLE EMPLOYEE PERFORMANCE - Rahman Hadi; Tine Yuliantini (Bajang Institute, 2026)
This study examines the effects of responsible leadership, organizational culture, and workload on employee performance, with intrinsic motivation serving as a mediating variable. The research was conducted at PT Yodya Karya (Persero), a state-owned enterprise operating in the construction consulting sector, using a census (saturated) sampling method that produced 250 valid responses. Employing a quantitative, cross-sectional design, data were collected through validated questionnaires and analyzed with Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings indicate that responsible leadership, organizational culture, and workload have positive and significant effects on intrinsic motivation, while these variables—together with intrinsic motivation—positively and significantly influence employee performance. Furthermore, intrinsic motivation significantly mediates the relationships between responsible leadership, organizational culture, and workload, and employee performance. These results provide empirical evidence that strengthening responsible leadership practices, fostering a supportive organizational culture, and maintaining proportional workload are critical strategies for sustaining intrinsic motivation and enhancing employee performance in state-owned construction consulting enterprises.